PENGEMBANGAN SISTEM PENJUALAN DAN PERSEDIAAN BARANG BERBASIS DESKTOP PADA USAHA DAGANG AFEN - Nanda, Bunga; Kristina, Kristina; Antonius, Antonius (LPPM Universitas Widya Dharma Pontianak, 2024)
Usaha Dagang Afen is a is a business that sells various accessories such as: wallets, bags, jewelry boxes and so on. This business has not yet implemented a computerized based information system and has not used a database as a storage. Usaha Dagang Afen still uses a conventional system where there is no record of incoming, outgoing, and quantity of goods, so there is often a shortage or shortage of unknown goods which hinders selling, and inaccurate accounts receivable. The method of data collection carried out by the author is by interview, observation and literature study. The analysis technique used is an object-oriented analysis technique with the Unified Modeling Language (UML) as the modeling language and StarUML Ver 5.0.2.1570 as the modeling application. The system design application used is Microsoft Visual Studio 2010 as the programming language, MySQL ODBC 5.3 Unicode Driver, XAMPP Control Panel ver 3.3.0, MySQL ver 8.0 as the system design and database processing application. Based on the results of the research conducted, the authors produced a desktop based selling and inventory application that helps minimize the occurrence of incomplete invoices and uncontrolled inventory. Keywords — Analysis, Design, Information System, Selling, Inventory